Management of Asthma and COPD Exacerbations in Adults in the ICUKey PointsClinical QuestionClinical Question - Stephen A. Mein, MD; Michael C. Ferrera, MD (CHEST Critical Care)
Severe, life-threatening asthma and COPD exacerbations are managed commonly in the ICU and are associated with significant morbidity and mortality. It is important to understand the commonalities and differences in the diagnosis and management of these obstructive lung diseases to improve patient outcomes via evidence-based care. In this review, we first outline triggers of acute asthma and COPD exacerbations and an initial diagnostic evaluation and severity assessment. We then review the pathophysiologic features of asthma and COPD exacerbations and create a framework for the management of exacerbations in critically ill adult patients aimed at reducing airway inflammation, reversing bronchospasm, and, in severe cases, supporting patients with mechanical ventilation or advanced therapies until clinical improvement is achieved.